Analysis of the Effect of Profitability on General Corporate Information and Forward-looking Information and its impact on the Company's Share Prices listed on the Indonesia Stock Exchange - Nur Ahmadi Bi Rahmani; Azhar Maksum; Khaira Amalia Fachrudin; Amlys Syahputra Silalahi (AIBPM Publisher, 2020)
Many cases of investors who experience losses in investing by buying company shares have led to thoughts about what information is actually needed by investors in reducing the possibility of mistakes. The purpose of this research is to find and create the latest model of information that should be conveyed to reduce the occurrence of multi-interpretation of information. The population used is 540 companies listed on the Stock Exchange with the criteria of having active financial and web reports at the time of the study, then the target population becomes 302 with the sampling method using saturated samples then the entire target population is sampled as many as 302 companies. The analysis used is path analysis using the smart PLS tool, The researcher managed to make a finding that at alpha five percent, profitability directly had a positive and significant effect on general corporate information, and stock prices, but not on foward-looking information. General corporate information directly affects the stock price while foward-looking information does not significantly influence the stock price. Indirectly, profitability has a positive and significant effect on stock prices through general corporate information, but not through foward-looking information.